2021
DOI: 10.1088/1755-1315/762/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic purity and population structure of potato variety Granola L

Abstract: The phenotypic performances have formed the basis for genetic purity evaluation. However, the phenotypic based the genetic purity assessment are time-consuming, expensive, and not stable due to a great environmental effect on traits expression. While, the genotypic based genetic purity evaluation of a variety offers an efficient, more stable, and precise result than those phenotypic method due to no environmental factors involved. The objectives of this study were to determine genetic purity and population str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Granola L. variety which is popular and widely cultivated in Indonesia has been reported to have phenotypic changes in the field [21]. To solve this challenge, Kirana et al [21] has studied about genetic purity and population structure of Granola L. variety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granola L. variety which is popular and widely cultivated in Indonesia has been reported to have phenotypic changes in the field [21]. To solve this challenge, Kirana et al [21] has studied about genetic purity and population structure of Granola L. variety.…”
Section: Introductionmentioning
confidence: 99%
“…Granola L. variety which is popular and widely cultivated in Indonesia has been reported to have phenotypic changes in the field [21]. To solve this challenge, Kirana et al [21] has studied about genetic purity and population structure of Granola L. variety. It is reported that between all the Granola L. samples that were taken from several location in Indonesia, had high level of genetic purity and consisted of 2 sub-population.…”
Section: Introductionmentioning
confidence: 99%